Peningkatan Pengetahuan dan Keterampilan Pengukuran Tekanan Cuff Pipa Endotrakeal Perawat Intensif Menggunakan Metode Simulasi dan Demonstrasi - Fauzan Alfikrie; Achir Yani S. Hamid; Muhammad Syafwani (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Maintaining cuff pressure in the ideal range is the responsibility of nurse. This is needed to prevent the occurrence of complications caused by cuff pressure that is not ideal such as ischemia in the trachea and micro-aspiration.Objective: this study identified the effect of training toward nurse’s knowledge and skills intensive care unit in measuring endotrakeal tube cuff pressureMethod: This study used the quas experiment design with the pre-posttest method without control group design and analyzed statistically using the Wilcoxon test.Result: The results of the research conducted were twelve nurses in the intensive care unit at the regional general hospital in dr. Soedarso Pontianak showed a significant difference in knowledge (p 0.002, α 0.05) and skills (p 0.002, α 0.05) before and after training in endotracheal tube cuff pressure training.Conclussion: The researcher recommends that the measurement of cuff pressure be carried out in accordance with the indications so that it is expected to reduce the risk of complications caused